1987
DOI: 10.1055/s-2007-1020229
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Prophylaxis in Cardiovascular Surgery

Abstract: In the past five years three prospective randomized studies compared five different prophylactic antimicrobial regimens in major cardiovascular surgery. In 1980/81 a 4 d cefazolin (CFZ) prophylaxis (16 X 0.5 g) was compared with a 2 d cefuroxime (CFX) administration (4 X 1.5 g). Of the 566 patients who entered the study 281 received CFZ and 285 were given CFX. In 1982/83 a 2 d CFX prophylaxis (4 X 1.5 g) was compared with a two shot ceftriaxone (CRO) prophylaxis (2 g i.v., + 1 g 24 h later). Of the 512 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Stone et al [17] randomized post-operative antibiotics versus placebo for patients who had received appropriate pre-operative antibiotics, and found no benefit in elective gastrointestinal and biliary surgery. The data for cardiothoracic surgery [18][19][20][21][22][23][24], total joint replacement [25][26][27][28], peripheral vascular surgery [29,30], colorectal surgery [31][32][33][34][35], and hysterectomy [36][37][38] have consistently demonstrated no value in improving the rates of SSI if antibiotics are continued well into the post-operative period. McDonald et al [39] performed an extensive meta-analysis across all specialties in surgery and demonstrated no difference between single-dose pre-operative antibiotics and pre-operative antibiotics and multiple post-operative doses of the drug.…”
Section: Duration Of Postoperative Administrationmentioning
confidence: 99%
“…Stone et al [17] randomized post-operative antibiotics versus placebo for patients who had received appropriate pre-operative antibiotics, and found no benefit in elective gastrointestinal and biliary surgery. The data for cardiothoracic surgery [18][19][20][21][22][23][24], total joint replacement [25][26][27][28], peripheral vascular surgery [29,30], colorectal surgery [31][32][33][34][35], and hysterectomy [36][37][38] have consistently demonstrated no value in improving the rates of SSI if antibiotics are continued well into the post-operative period. McDonald et al [39] performed an extensive meta-analysis across all specialties in surgery and demonstrated no difference between single-dose pre-operative antibiotics and pre-operative antibiotics and multiple post-operative doses of the drug.…”
Section: Duration Of Postoperative Administrationmentioning
confidence: 99%
“…Abdominal surgery is thought to be a risk factor for CDAD,7 and post-surgical CDAD has been well described. The reported rates of post-surgical CDAD range from 0.2% to 8.4% depending on the surgical population studied and types of operations performed 7-13. No study has been reported, however, that compares post-surgical CDAD and medical CDAD with respect to risk factors and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical wound infections were analyzed in 40 of these studies (n = 13,303 patients), respiratory tract infections in 25 (n = 9,567 patients), and urinary tract infections in 24 (n = 8,865 patients). 17 studies were excluded from further analysis [3,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Resultsmentioning
confidence: 99%